Optimization and characterization of biosurfactant produced by Pseudomonas sp. LM19 using palm kernel fatty acid distillate - Thio, Cui Wen (2019)
Biosurfactants were used in various industries owing to their high biodegradability and low toxicity. However, biosurfactant applications are still limited due to its high production cost and low production. This obstacle can be overcome by optimizing the fermentation condition to increase production yield, while simultaneously exploiting potential low-cost materials as substrate to reduce production cost. In Malaysia, growing production of palm oil and its downstream products resulted in a surplus of low value oleochemical products such as palm kernel fatty acid distillate (PKFAD). Therefore, the first objective in this study was to determine the optimum fermentation conditions for biosurfactant production by indigenous Pseudomonas sp. LM19 using PKFAD as carbon source. The second objective was to characterize the biosurfactants produced using analytical and physical properties characterization techniques. Fermentation conditions including the incubation temperature, inoculum size, PKFAD concentration, pH, agitation speed, and incubation time were screened and optimized. Factors ranges were set using the preliminary experiments in a combination of one-factor-at-a-time (OFAT) and two-level full factorial designed experiments based on conditions reported by peer studies. These factors were then optimized using response surface methodology (RSM). A full randomized factorial design with thirty experimental runs was suggested by Design Expert Software to assist the identification of optimum fermentation conditions. Responding variables chosen for both preliminary and optimization experiments were emulsification index (E24) and rhamnolipid concentration quantified via orcinol test. From the study, the optimum conditions obtained from RSM were pH 7.5, 2% (v/v) PKFAD, agitation speed of 170 rpm and 192 h of incubation time with E24 of 58.6 ± 0.62% and biosurfactant concentration of 1.6 ± 0.01 g/L. The produced biosurfactant was then characterized to identify the features of biosurfactant. Thin layer chromatography (TLC) indicated that the biosurfactant produced was found to be glycolipid as it showed the presence of both lipid and sugar moieties. Two spots were obtained with Rf values of 0.68 and 0.38, being mono-rhamnolipid and di-rhamnolipid, respectively. Similar findings were resonated by Fourier transform infrared (FTIR) spectroscopy and nuclear magnetic resonance (NMR) analysis as both tests complemented each other to confirm the presence of an ester bond linking aliphatic chain to saturated carboxylic group, a trademark functional group in glycolipids. NMR results further revealed the presence of various functional groups present in rhamnolipid molecules, indicating the glycolipid biosurfactant was rhamnolipid in nature. Gas chromatography mass spectrometry (GCMS) recorded the presence of the pseudo-molecular ion, two methyl-esterified fatty acids in the form of β-hydroxy fatty acids. High performance liquid chromatography equipped with quadruple photodiode and evaporative light scattering detector (HPLC-QDa-ELSD) was then used to determine the rhamnolipid congeners. The rhamnolipid produced by Pseudomonas sp. LM19 were di-rhamnolipid dominant, containing 57.42% of the sample while the rest were mono-rhamnolipids. Antimicrobial activity and surface tension test were conducted to identify the functional properties of the rhamnolipid produced. Rhamnolipid produced was able to inhibit the growth of Bacillus subtilis. The surface tension test indicated that the rhamnolipid produced exhibited a critical micellar concentration (CMC) of approximately 28 mg/L. To conclude, the biosurfactant production by Pseudomonas sp. LM19 using PKFAD as substrate was optimized, with its preferred fermentation conditions of pH 7.5, 2% (v/v) PKFAD, agitation speed of 170 rpm and 192 h of incubation time. The biosurfactant produced was extracted and characterized as type of rhamnolipid biosurfactant, containing di-rhamnolipid dominant with C10-C10 lipid chains, exhibited CMC of 28 mg/L.